Modified multivariate cumulative sum control chart based on robust estimators - Razale, A. S.; Ali, N. M.; Ali, N.; Rahmin, N. A. A. (Malaysian Mathematical Science Society (PERSAMA), 2023)
Integrate several robust approaches to the classical MCUSUM control chart. These approaches used robust location and scale estimator to substitute the usual mean and covariance matrix, respectively into the classical MCUSUM. The two robust location estimators used are the modified one-step M estimator (MOM) and Hodges Lehmann estimator (HL). Then, a scale estimator named Madn was introduced and functioned accordingly to the robust location estimators. Altogether, two robust MCUSUM control charts were proposed.